Implementasi Program Kampus Mengajar di Sekolah Dasar - Lestari, Agus (SAP (Susunan Artikel Pendidikan), 2024)
This study evaluated the impact of the Kampus Mengajar program as part of the Merdeka Belajar Kampus Merdeka (MBKM) program on the improvement of literacy and numeracy skills on elementary school students. A mixed-methods approach was used, involving university students, teachers, and Elementary students in the learning process. The results of literacy and numeracy tests showed a significant increase in average scores in all classes involved. Interviews and observations revealed that students played an active role in learning innovation, providing additional motivation, and improving the quality of teaching. Supporting factors, such as school principal support and program integration into the curriculum, supported the success of implementation. However, time and resource constraints posed challenges that needed to be addressed. In conclusion, the Kampus Mengajar program has the potential to make a positive contribution to the improvement of student literacy and numeracy skills, and program development recommendations are given to improve its effectiveness in the future. These findings provide an empirical basis to support similar initiatives and contribute to the education literature in Indonesia.